Blowing and in-situ activation of carbonaceous "lather" from starch: Preparation and potential application. (15th February 2016) - Lei, Hong; Chen, Danfeng; Huo, Jichuan
Abstract: Activated carbon foam with nano-thickness cell walls (ACF-NCW) is prepared via a simple method. Starch, a natural polysaccharide, is selectively hydrolyzed by mixed-acid firstly. Then, the hydrolyzed starch is dried and mixed with zinc chloride. Finally, ACF-NCW can be prepared with the assistance of microwave irradiation under the synergistic effect of foaming, carbonization and in situ activation. Different from the traditional carbon foams, the ACF-NCW possesses the characteristic of three-dimensional (3D) graphene and porous carbon nanosheet. Its porous cell walls are in the thickness of 50 nm, which shorten the transmission distance of ions during its application. The laminated polycrystalline walls and 3D interconnected structure are propitious to electron transfer. Due to its large specific surface area (BET: 926 m 2 /g, DFT: 730 m 2 /g), the ACF-NCW electrode exhibits high specific gravimetric capacitance of 172 F/g at 0.5 A/g in 6 mol/L KOH and good electrochemical stability with gravimetric capacitance retention up to 92% after 1000 cycles at 2.5 A/g. Graphical abstract: Highlights: Activated carbonaceous "lather" was prepared from starch. The structure of the material was different from the traditional carbon foams. With porous thin cell walls, the material has large specific surface area. The material has large porosity, channels for mass transfer and good conductivity.